Harriet Tubman : the life of an African-American abolitionist - Shone, Rob.; Ganeri, Anita, 1961- (London : Watts, 2007)
Examines the life of Harriet Tubman, an escaped slave who risked her freedom to help other slaves along the Underground Railroad. Presented in graphic novel form.
Who's who -- The Underground Railroad -- Harriet Tubman's world -- Harriet Tubman : the life of an African-American abolitionist -- Freedom!
Includes bibliographical references (p. 47) and index.
5.0
5-8
Keywords: Tubman, Harriet, -- 1820?-1913 -- Comic books, strips, etc. -- Juvenile literature; Tubman, Harriet, -- 1820?-1913 -- Cartoons and comics; Tubman, Harriet, -- 1820?-1913 -- Comic books, strips, etc; African American abolitionists -- Biography -- Comic books, strips, etc. -- Juvenile literature; African American women -- Biography -- Comic books, strips, etc. -- Juvenile literature; African Americans -- Biography -- Comic books, strips, etc. -- Juvenile literature; Slaves -- United States -- Biography -- Comic books, strips, etc. -- Juvenile literature; Underground railroad -- Comic books, strips, etc. -- Juvenile literature; African Americans -- Biography -- Cartoons and comics; Cartoons and comics; Slaves -- Cartoons and comics; Underground railroad -- Cartoons and comics; African Americans -- Biography -- Comic books, strips, etc; Comic books, strips, etc; Slaves -- United States -- Biography -- Comic books, strips, etc; Underground railroad -- Comic books, strips, etc